Manhaj Interpretations From Classic To Contemporary - Havis Aravik; Choiriyah Choiriyah; Fadilla Fadilla; Dwi Noviani (Publication and Inovasi Research, 2025)
Tafsir of the Qur'an from classical to contemporary periods has developed in the manhaj (method) used to reveal the meaning of revelation. The problem discussed in this research is the difference in manhaj tafsir from classical to contemporary, as well as the influence of changes in methods on understanding of the Qur'an. The purpose of this research is to analyze the development of manhaj tafsir, both tahlili (analytical) and with al-ray (rational) approach, as well as to compare the works of tafsir that reflect each of these methods. The method used in this research is a literature review with an analytical descriptive approach, by examining several works of tafsir such as Jami' al-Bayan fi Tafsir al-Qur'an by al-Thabari, Tafsir al-Qur'an al-Karim by Ibn Katsir, Al-Kasysyaf by Az-Zamakhshari, Tafsir al-Manar by Abduh and Rashid Ridha, as well as contemporary tafsir such as Tafsir Al-Misbah by M. Quraish Shihab. The results show that the change in manhaj tafsir, from the use of history (bi al-ma'tsur) to the rational approach (al-ray), reflects the dynamics of Islamic thought that continues to develop, with different emphasis on social, intellectual, and methodological contexts..